Precariat, education and technologies: Towards a global class identity. (8th November 2015) - Standing, Guy; Jandrić, Petar
In this interview Guy Standing outlines the main links between the precariat and the universal basic income. He briefly comments on the relationships of his work to traditional Marxism, and expands his critique of the precariat towards information and communication technologies. He identifies common features of the global precariat, and links them to creation of a common global class identity. Moving on to transformative potentials of the universal basic income, he dismisses ancient labels and frameworks as unnecessary and potentially misleading, and calls for reinvention of the contemporary language of progress. Finally, he seeks critical emancipation of the precariat in urgent decommodification of all aspects of education and information.